Transplacental passage of hyperforin, hypericin, and valerenic acid - Deborah Spiess; Deborah Spiess; Vanessa Fabienne Abegg; Antoine Chauveau; Joshua Rath; Andrea Treyer; Michael Reinehr; Sabrina Kuoni; Mouhssin Oufir; Olivier Potterat; Matthias Hamburger; Ana Paula Simões-Wüst (Frontiers Media S.A., 2023)
Safe medications for mild mental diseases in pregnancy are needed. Phytomedicines from St. John's wort and valerian are valid candidates, but safety data in pregnancy are lacking. The transplacental transport of hyperforin and hypericin (from St. John's wort), and valerenic acid (from valerian) was evaluated using the ex vivo cotyledon perfusion model (4 h perfusions, term placentae) and, in part, the in vitro Transwell assay with BeWo b30 cells. Antipyrine was used for comparison in both models. U(H)PLC-MS/MS bioanalytical methods were developed to quantify the compounds. Perfusion data obtained with term placentae showed that only minor amounts of hyperforin passed into the fetal circuit, while hypericin did not cross the placental barrier and valerenic acid equilibrated between the maternal and fetal compartments. None of the investigated compounds affected metabolic, functional, and histopathological parameters of the placenta during the perfusion experiments. Data from the Transwell model suggested that valerenic acid does not cross the placental cell layer. Taken together, our data suggest that throughout the pregnancy the potential fetal exposure to hypericin and hyperforin - but not to valerenic acid - is likely to be minimal.